The impossibility of ideal motherhood : the psychological experiences and discourse on motherhood amongst South African low-income coloured mothers specifically in the Kylemore community - Youngleson, Annemarie (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Psychology))--University of Stellenbosch, 2007.